2005
DOI: 10.1021/bi051555f
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of Yeast Plasma Membrane H+-ATPase during Activation by Glucose:  Role of Threonine-912 in the Carboxy-Terminal Tail

Abstract: Yeast Pma1 H(+)-ATPase, which belongs to the P-type family of cation-transporting ATPases, is activated up to 10-fold by growth on glucose, and indirect evidence has linked the activation to Ser/Thr phosphorylation within the C-terminal tail. We have now used limited trypsinolysis to map glucose-induced conformational changes throughout the 100 kDa ATPase. In the wild-type enzyme, trypsin cleaves first at Lys-28 and Arg-73 in the extended N-terminal segment (sites T1 and T2); subsequent cleavages occur at Arg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 39 publications
2
43
0
Order By: Relevance
“…Removal of the last 18 amino acids by mutagenesis led to constitutive activation of the ATPase even in the absence of glucose (8,9). Consistent with this observation, immuno-blotting with anti-C-terminal antibody revealed that the C terminus was relatively inaccessible during carbon starvation but could be rapidly digested by trypsin upon the addition of glucose (10). Of added significance was the fact that amino acid substitutions within the tail, especially at Thr-912, reduced glucose activation in a manner that could be suppressed by second-site mutations elsewhere in the 100-kDa protein (11,12).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…Removal of the last 18 amino acids by mutagenesis led to constitutive activation of the ATPase even in the absence of glucose (8,9). Consistent with this observation, immuno-blotting with anti-C-terminal antibody revealed that the C terminus was relatively inaccessible during carbon starvation but could be rapidly digested by trypsin upon the addition of glucose (10). Of added significance was the fact that amino acid substitutions within the tail, especially at Thr-912, reduced glucose activation in a manner that could be suppressed by second-site mutations elsewhere in the 100-kDa protein (11,12).…”
supporting
confidence: 53%
“…Significantly, the C-terminal tail of Pma1 ATPase was relatively inaccessible to trypsin in samples from carbon-starved cells but rapidly degraded in samples from glucose-metabolizing cells. Substitution of Thr-912 by Ala led to arrest of the ATPase in the former state, whereas substitution by Asp led to arrest in the latter state (10). Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Otherwise the ATP concentration should decrease to zero. The mechanism controlling the activity of these ATPases is presently a matter of speculation, but for PMA1 it has been shown that the activity is controlled by glucose (40,41). The activation (and presumably also the deactivation) involves a threonine and a serine residue at the C terminus, which are rapidly phosphorylated on activation (42) (and presumably dephosphorylated on deactivation).…”
Section: Discussionmentioning
confidence: 99%
“…Carbon sources regulate Pma1's phosphorylation state (Lecchi et al 2005), its ATPase activity (Serrano 1983), and its conformation (Miranda et al 2002) through residues S899, S911, and T912 in the C-terminal tail, which faces the cytosol (Eraso et al 2006;Lecchi et al 2007). We mutated S899, S911, and T912 to alanine, which cannot be phosphorylated, or to aspartic acid, which mimics constitutive phosphorylation.…”
Section: P-values Are the Binomial Distribution Of The Mean (D) Pma1mentioning
confidence: 99%